Spatial distribution and pollution assessment of heavy metals in the surface sediments of the Bohai and Yellow Seas. Issue 1 (15th September 2016) - Xu, Xiaoda; Cao, Zhimin; Zhang, Zhixun; Li, Rihui; Hu, Bangqi
Abstract: A total of 141 surface sediments were collected and analyzed for their geochemistry, total organic carbon, and grain size to assess the heavy metal pollution in the Bohai and Yellow Seas. The enrichment factor (EF) and geoaccumulation index ( I geo ) of Cu, Pb, Zn, Cr, Cd, Ni, As, and Hg were calculated to assess anthropogenic contamination, and the results suggest that moderate Pb, Cd, and As contamination occurs in the study area. Sediment quality guidelines were applied to assess the adverse biological effects of these metals. The spatial distribution of the mean Effects Range-Median quotient for the vast majority of the study area is between 0.1 and 0.5, indicating low impact and potential negative biological effects. Multivariate analysis indicates that Cu, Pb, Zn, Cr, and Ni resulted primarily from lithogenic sources, whereas As, Cd, and Hg were mainly attributed to anthropogenic sources. Highlights: We examined heavy metals of the Yellow and Bohai Seas surface sediments. SQGs indicated low biological risk to local environments. Cu, Pb, Zn, Cr, and Ni were mainly from lithogenic inputs nearby. As, Cd, and Hg were mainly from anthropogenic input.